Ultrasonic spectroscopy of copolymer based P(VDF-TrFE) composites with fillers on lead zirconate titanate basis. (August 2016) - Belovickis, J.; Samulionis, V.; Banys, J.; Silibin, M.; Solnyshkin, A.; Shilyaeva, Yu.; Nekludov, К.; Gavrilov, S.; Rubanik, V.; Rubanik, V.; Shvartsman, V.V.
Abstract: In this work we report on the ultrasonic and dielectric properties of composites consisting of conventional piezoelectric polymer, polyvinylidene fluoride/trifluoroethylene (PVDF-TrFE) copolymer of composition 70/30 mol. %, and (Pb0.75 Ba0.24 Sr0.01 )(Zr0.53 Ti0.47 )O3 (BPZT) particles. BPZT fillers concentration was varied from 10 to 50 vol.%. Investigation of ultrasonic wave attenuation, velocity and piezoelectric voltage in these composites was performed over a temperature range from 300 K to 420 K using an automatic ultrasonic pulse-echo method. The temperature dependences of ultrasonic velocity and attenuation showed anomalies attributed to the glass transition temperature Tg and Curie temperature Tc of the polymer matrix.